2022
DOI: 10.3390/medicina59010099
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Brain-Derived Neurotrophic Factor (BDNF) Protein Level and Body Mass Index

Abstract: Background and Objectives: Obesity is a major health concern worldwide. Many studies emphasize the important role of brain-derived neurotrophic factor (BDNF) in regulating appetite and body weight. We aimed to investigate the association between BDNF protein serum levels and body mass index (BMI). Materials and Methods: We conducted a cross-sectional study among 108 healthy adult participants divided into six categories depending on their body mass index (BMI). The ages of the participants ranged between 21 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Masataka Suwa et al found a positive correlation between serum BDNF level and BMI in female diabetic patients [18] . A study found that people with different BMI levels have different serum BDNF levels, with underweight being the highest, followed by normal BMI, and the higher the degree of obesity, the lower the level of BDNF [19] . However, the results of this study showed that there was no significant difference in the degree of BDNF level increase in patients with different degrees of obesity after bariatric surgery, which may be related to the small sample size of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Masataka Suwa et al found a positive correlation between serum BDNF level and BMI in female diabetic patients [18] . A study found that people with different BMI levels have different serum BDNF levels, with underweight being the highest, followed by normal BMI, and the higher the degree of obesity, the lower the level of BDNF [19] . However, the results of this study showed that there was no significant difference in the degree of BDNF level increase in patients with different degrees of obesity after bariatric surgery, which may be related to the small sample size of the study.…”
Section: Discussionmentioning
confidence: 99%
“…A study of serum BDNF levels in severely obese patients from Saudi Arabia showed a significant correlation between a low BDNF expression and a high BMI. 56 A negative correlation also was found between plasma BDNF levels and IR. Similar results were obtained in experimental animals with diabetes and obesity.…”
Section: Receptorsmentioning
confidence: 92%
“…Modern research progress has played a significant role in sustaining high levels of healthcare and general well-being. Although conventional technologies like real-time polymerase chain reaction (RT-PCR) [ 1 , 2 ], enzyme-linked immunosorbent assay (ELISA) [ 3 ], high-performance liquid chromatography (HPLC) [ 4 ], gas chromatography–mass spectrometry (GCMS) [ 5 ], and so on demonstrate high sensitivity and accuracy, the complex and costly equipment required could cause a delay in response time. This highlights the essential need in biosensor and bioassay research for the development of rapid, portable, and user-friendly assays that could accelerate the diagnostic process and alleviate treatment delay [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%